SOCIAL ARCHETYPES IN LINGUISTIC COMMUNICATION CULTURE - M. Tursunova (Sciental Journals Publishing, 2025)
Language is a living artifact of human culture, intricately woven with the identities, roles, and power dynamics that define social life. Within this tapestry, social archetypes emerge as recurring patterns—prototypical figures like the "hero," "trickster," "caregiver," or "outsider"—that shape how individuals communicate and interpret meaning. These archetypes are not mere literary devices but active forces in linguistic communication culture, influencing syntax, lexicon, and discourse norms. This article offers an in-depth examination of social archetypes, exploring their origins, manifestations across contexts, cultural variations, and broader implications for understanding language as a social phenomenon.
Keywords: Archetypes, language, concept, unconscious, sociolinguist, speech, linguistic communication, cultural norms, gender norms.